2015
DOI: 10.1002/jpln.201400476
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates cold‐induced oxidative damage in maize seedlings by up‐regulating mineral elements and enhancing antioxidant activity

Abstract: Melatonin, known as an animal hormone and an antioxidant with a low molecular weight, is one of the most commonly used substances to improve plant resistance against various environmental stresses. However, there are no studies explaining the effects of melatonin on the relationship between defense system and mineral composition of plants under stressed and unstressed-conditions. The present study was conducted to investigate whether the mitigating effect of melatonin is associated with its modulating influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…Calcium also plays an important role in cell wall structure and tissue firmness. Melatonin application led to a reduction in water loss and an increase in calcium content in maize seedlings under cold stress [18]. The weight loss and reduced decay elicited by melatonin treatment in chilled strawberry fruit shown here could therefore possibly be due to redistribution of the calcium in strawberry fruit tissue leading to less moisture loss.…”
Section: Weight Loss and Decay Are Significantly Affected By Treatmenmentioning
confidence: 65%
“…Calcium also plays an important role in cell wall structure and tissue firmness. Melatonin application led to a reduction in water loss and an increase in calcium content in maize seedlings under cold stress [18]. The weight loss and reduced decay elicited by melatonin treatment in chilled strawberry fruit shown here could therefore possibly be due to redistribution of the calcium in strawberry fruit tissue leading to less moisture loss.…”
Section: Weight Loss and Decay Are Significantly Affected By Treatmenmentioning
confidence: 65%
“…These observations indicate that melatonin might serve as a second messenger, activating downstream cold-responsive genes including EnCBF9, EnCBF14 , and EnCOR14a , and thus stimulating biosynthesis of cold-protecting compounds. Consequently, this contributes to the enhancement of cold tolerance in plants treated with exogenous melatonin and subjected to cold stress2331. Previous studies reported that both cold treatment and exogenous ABA treatment induce the expression of CBF1 and several COR genes in A. thaliana plants4344.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, melatonin has been found to be a ubiquitous modulator in multiple plant developmental processes, including flowering, promotion of photosynthesis, preservation of chlorophyll17, stimulation and regeneration of root system architecture18, delayed senescence of leaves19, and alleviation of oxidative damage induced by reactive oxygen species (ROS) and reactive nitrogen species (RNS)1720. Moreover, melatonin is involved in the regulation of various abiotic stresses, such as cold212223, salinity24, heavy metal25, herbicides26, and UV radiation27. The mechanisms of melatonin-mediated stress tolerance involve the activation of antioxidants biosynthesis and activities of antioxidant enzymes, as well as the direct scavenging of ROS following plant exposure to harsh environments282930.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The leaf relative water concentration (RWC) was estimated by following Turk and Erdal (2015). The fresh weight (FW) of the seventh leaf was measured immediately after sample harvesting.…”
Section: Determination Of Leaf Relative Water Content (Rwc)mentioning
confidence: 99%